Ghosts of the Somme : commemoration and culture war in Northern Ireland - Evershed, Jonathan; Evershed, Jonathan (University of Notre Dame Press, 2018)
"In 2016, as the Irish Republic marked the hundredth anniversary of its sacrificial founding by the martyrs of Easter week, Ulster Loyalists were making final preparations to mark the centenary of a blood sacrifice of equal and opposite significance for contemporary Irish politics: that of the 36th (Ulster) Division at the Battle of the Somme during World War I. This book examines the complex politics of commemorating Ireland's 'other' 1916. During the present 'Decade of Centenaries, ' commemoration - viewed as a driver or even cause of past conflict in Northern Ireland - has come to occupy a central place in ongoing efforts at peacebuilding and reconciliation. Drawing on more than 18 months of original ethnographic field work conducted in Belfast, this book examines the conflicted politics of Ulster Loyalist commemorations of the Battle of the Somme during the Decade. In a context defined for Loyalists by what they have termed the 'culture war, ' commemoration is the means by which they confront and challenge the perceived erosion of their identity in the 'new' Northern Ireland. Evershed examines how commemoration of the Somme brings Loyalists into conflict not only with the politics of Irish Nationalism, but with the 'peacebuilding' state and, crucially, with each other."--Provided by publisher.